2019
DOI: 10.3354/aei00309
|View full text |Cite
|
Sign up to set email alerts
|

Application of polychaetes in (de)coupled integrated aquaculture: production of a high-quality marine resource

Abstract: However, the predicted expansion of the aquaculture sector generates several environmental concerns (Ottinger et al. 2016). For example, discharges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 83 publications
(103 reference statements)
4
30
0
Order By: Relevance
“…Given their small size, Dorvilleids have never been an important commercial group. However, a recent study suggested the beneficial use of Ophryotrocha species in pisciculture by feeding on fish feces and in turn being fed to the fish [117]. In addition, because they have a short generation time and are easily kept in laboratory conditions, Ophryotrocha species may be suitable candidates as test model organisms for various kinds of studies [70,79,87,118].…”
Section: Exploitationmentioning
confidence: 99%
“…Given their small size, Dorvilleids have never been an important commercial group. However, a recent study suggested the beneficial use of Ophryotrocha species in pisciculture by feeding on fish feces and in turn being fed to the fish [117]. In addition, because they have a short generation time and are easily kept in laboratory conditions, Ophryotrocha species may be suitable candidates as test model organisms for various kinds of studies [70,79,87,118].…”
Section: Exploitationmentioning
confidence: 99%
“…Trays were placed (a) on the south side of each of the 8 salmon cages, and (b) additional trays were placed on the north side below cages 1, 2, 4 and 8. The quality of video recordings of Tray 1a, 2b and 5a was not sufficient for categorizing the tray coverage and they were therefore omitted and thereby in waste decomposition (Salvo et al 2015, Nederlof et al 2019. Either way, Eikje (2013) re ported a significant increase in population size throughout a salmon production cycle but also a steep decrease after the fish were harvested and orga nic loading disappeared.…”
Section: Succession Of Polychaete Communities Under Fish Farmsmentioning
confidence: 99%
“…The production potential of O. craigsmithi under laboratory conditions (Nederlof et al 2019) is high in comparison to Nereis virens used in recirculating aquaculture systems and pond-integrated aquaculture (Brown et al 2011), or to soft-sediment opportunistic Capitella spp. cultured under a shallow fish farm in Japan (Kinoshita et al 2008).…”
Section: Perspective For Integrated Benthic Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…Marine polychaetes have been often pinpointed as holding great potential to recover wasted nutrients from POM with species such as Hediste diversicolor 9 , 20 25 , Perinereis aibuhitensis 26 , Alitta virens 26 , 27 , Perinereis nuntia 28 , 29 , Perinereis helleri 29 , 30 , Arenicola marina 26 , Abarenicola pusilla 31 , 32 , Capitella sp. and Ophryotrocha craigsmithi 33 already being tested under IMTA designs. These marine worms have already been successfully combined with organisms that may retain dissolved inorganic nutrients efficiently, such as macro and microalgae 22 , 23 , as well as halophytes 9 .…”
Section: Introductionmentioning
confidence: 99%